Perceived external prestige and perceived employee and organizational performance : the mediating role of organizational identification - Sarı, Tunahan (My University, 2020)
Çalışmanın ana değişkeni algılanan dışsal prestij, çalışanların o örgütün bir üyesi oldukları için o örgütte çalışmayan insanlar tarafından nasıl değerlendirilecekleri hakkındaki düşünceleri olarak tanımlanabilir. Bu çalışma, Sosyal Kimlik, Sosyal Sınıflandırma, Sosyal Karşılaştırma ve Sosyal Mübadele teorilerinden yola çıkarak algılanan dışsal prestijin, algılanan çalışan ve örgüt performansına etkisini incelemeyi amaçlamıştır. Bu ilişkiye ek olarak, örgütsel özdeşleşmenin aracılık rolü de araştırılmıştır. Algılanan çalışan performansı, rol içi performans ve rol dışı performans olarak iki kategori altında değerlendirilmiştir. Araştırmaya farklı endüstrilerden 299 özel sektör çalışanı katılmıştır. Basit doğrusal regresyon analizleri, algılanan dışsal prestijin örgütsel özdeşleşmeye ve çalışan ve örgüt performansına anlamlı ve pozitif katkısı olduğunu göstermiştir. Çoklu regresyon analizleri örgütsel özdeşleşmenin, algılanan dışsal prestij ve algılanan çalışan ve örgüt performansı arasındaki ilişkide kısmi aracı rolü olduğunu göstermiştir. Demografik değişkenler, bağımsız gruplar t-testleri ile test edilmiştir. Bu çalışma örgütsel özdeşleşmenin algılanan dışsal prestij ve algılanan çalışan ve örgüt performansı arasındaki ilişkideki aracı rolünü inceleyerek, algılanan dışsal prestij literatürüne katkı sağlayacaktır.

The main variable of this study, perceived external prestige, can be defined as employees’ thoughts about how people who do not work for this organization judge them because of their membership to this organization. Based on Social Identity, Social Categorization, Social Comparison, and Social Exchange theories, the current study aimed to examine the effect of perceived external prestige on perceived employee and organizational performance. In addition to this association, the mediating effect of organizational identification was also investigated. Perceived employee performance was evaluated under two categories, which are in-role and extra-role performance. A total of 299 private-sector employees from different industries participated in the study. The simple linear regression analyses showed that perceived external prestige has a significant and positive contribution to organizational identification, perceived employee, and organizational performance. The multiple regression analyses showed that organizational identification had a partially mediator role in the relationship between perceived external prestige and perceived employee and organizational performance. Demographic variables were tested through independent samples t-tests. This study will contribute to perceived external prestige literature by investigating the mediating role of organizational identification on the relationship between perceived external prestige and perceived employee and organizational performance.
Keywords: Algılanan Dışsal Prestij; Algılanan Örgütsel Performans; Algılanan Rol Dışı performans; Algılanan Rol İçi Performans; Business; İşletme; Organizational behavior; Organizational Identification; Örgütsel davranış; Örgütsel Özdeşleşme; Perceived External Prestige; Perceived Extra-role Performance; Perceived In-role Performance; Perceived Organizational Performance